PENINGKATAN KEMAMPUAN MENYIMAK BERITA MENGGUNAKAN STRATEGI START WITH A QUESTION PADA SISWA KELAS VII SMP YAKHALUSTI PONTIANAK TIMUR - Kalsum, Ummi; Priyadi, A. Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to obtain information on Improving the Listening Skills News Using Strategistart With A Questions In Grade VII Students of of Junior of Yakhalusti East Pontianak related to the implementation, evaluation and impact of learning to listen to news by using strategy start with a questions.The conclusions in this study are: 1) The application of the method in their learning process which is the strategy of â€œ Start With a Questionsâ€ on the studentof class VII B, Yakhalusti East Pontianak Primary Highscool has been accomplished as wishes. The result is based on the observation of first and second cycle. The shown result is absolutely by the observation that has been accomplished. 2) There are also an evalutionÂ for the learning process by using the strategy of â€œStart With A Questionsâ€ on the student of class VII B, Yakhalusti East Pontianak Primary Highscool has been successfully done exactcly with the evalution aspect before.. The average values of the studentâ€™s learning process has increasely twice from the 65,00 to 2,8 and 9,75 in total of 74,75 3) Besidens, the listening learning process by the strategy of â€œStart With a Questionsâ€ on student of class VII B, Yakhalusti East Pontianak Primary Hisghscool has increasely rose up than where obtained from cycle I with yield criteria 62,25% and cycle II.Â Keywords: improved, capability, news listening, SWQ strategyÂ